Novel α-Hydroxy γ-Butenolides of Kelp Endophytes Disrupt Bacterial Cell-to-Cell Signaling - Vallet, Marine; Chong, Yee-Meng; Tourneroche, Anne; Genta-Jouve, Grégory; Hubas, Cédric; Lami, Raphael; Gachon, Claire M. M.; Klochkova, Tatyana; Chan, Kok-Gan; Prado, Soizic (Frontiers in Marine Science, 2020)
A wide range of microbial symbionts such as bacteria and fungi colonize the tissues of macrophytes. The chemical interactions between these endophytes remain underexplored. The obligate marine fungus Paradendryphiella salina was isolated from several healthy brown macrophyte species. Novel α-hydroxy γ-butenolides produced by P. salina were purified and characterized by nuclear magnetic resonance (NMR). These compounds interfere with the bacterial quorum sensing system as shown in bioassays with pathogenic bacterial model Pseudomonas aeruginosa. Ultra-performance liquid chromatography–high-resolution mass spectrometry (UHPLC-HRMS)-based comparative metabolomics revealed the presence of the main α-hydroxy γ-butenolides among all the P. salina strains isolated from different hosts as well as a high metabolic variability related to the alga-host species. Collectively, these findings highlight the key role of microbial chemical signaling that may occur within the algal holobiont.